Effects on mouse spermatogenesis and DNA fragmentation following exposure to cyclophosphamide and thymoquinone - Saheera, Kamarzaman; Sha'ban, Munirah; Abdul Rahman, Suzanah (Center for Enhancing Knowledge (CEK), 2013)
The potential of thymoquinone, an active component of Nigella Sativa, in lowering chemotherapeuticassociated toxicity of cyclophosphamide in the testis, epididymis and sperm DNA of adolescent male mice was investigated. Cyclophosphamide and thymoquinone were administered intraperitoneally by a single injection at 200 mg/kg and 10 mg/kg on alternate days, respectively. Effects were observed on days 5, 32 and 53. Results show that thirty-two days following exposure to cyclophosphamide, the spermatogonia cells was reduced by 52% than that in the control group, p<0.05. Treatment with cyclophosphamide also induced significant toxicity as shown by hypertrophy in the mean diameter of seminiferous tubules and tubular lumen (p<0.05), vacuolization of spermatogonial layers and destruction of interstitial tissues. Administration of thymoquinone exhibited significant reduction in overall toxicity caused by cyclophosphamide. The integrity of the seminiferous tubule was well preserved and the numbers of total DNA damaged cells were reduced from 49% to 4% at 32 days.